BUILDING BUSINESS AGILITY OF INDONESIAN MSMES: THE ROLE OF DIGITAL LITERACY AND ENTREPRENEURSHIP ORIENTATION (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy, particularly in employment generation and contribution to Gross Domestic Product (GDP). In the digital era, MSMEs are required to possess adaptive capabilities to survive and compete in an increasingly dynamic business environment. This study aims to analyze the role of digital literacy and entrepreneurial orientation in shaping MSME business agility in Indonesia. The research employs a quantitative explanatory approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The study population consists of MSME actors who have adopted digital technology in their business activities, with respondents selected through purposive sampling techniques. The findings indicate that digital literacy has a positive and significant effect on business agility with a path coefficient value of 0.318 and a t-statistic of 3.912. Digital literacy also positively influences entrepreneurial orientation with a path coefficient of 0.764 and a t-statistic of 12.871. Furthermore, entrepreneurial orientation has a positive and significant effect on business agility with a path coefficient of 0.547 and a t-statistic of 6.438. The mediation test results reveal that entrepreneurial orientation significantly mediates the relationship between digital literacy and business agility, with an indirect effect value of 0.418 and a t-statistic of 5.731. These findings confirm that digital literacy and entrepreneurial orientation are essential factors in improving MSME adaptability amid digital economic transformation. This study contributes theoretically by developing an integrated model that explains the relationship between digital literacy, entrepreneurial orientation, and MSME business agility in the context of developing countries.